Dismembered pyeloplasty for ureteropelvic junction syndrome treatment in children - João Moreira-Pinto; Angélica Osório; Fernando Vila; João Luís Ribeiro de Castro; Armando Réis (Wolters Kluwer Medknow Publications, 2012)
Background: Open dismembered pyeloplasty remains the preferred surgical technique for ureteropelvic junction syndrome (UPJS) in most paediatric urology units. The authors present their experience of 230 patients and describe their form of presentation, treatment and early and long-term results. Materials and Methods: Retrospective analysis of clinical records of 230 patients submitted to dismembered pyeloplasty in an 8-year period, from 1999 until 2007. Pre-operative data, early and long-term complications were registered. Image studies included renopelvic ultrasonography, mercapto-acetyl triglycine (MAG3) renal scan with furosemide test and, in some cases, elimination urography and retrograde cystography. Pre-operative and post-operative results were compared. Results: Median age of our patients at time of surgery was 14.9 months (range: 21 days until 16.6 years). The majority of patients were male (72%, n = 166) and 74% (n = 120) had pre-natal diagnosis. The majority of hydronephrosis were in the left side (61%, n = 141). There were only 3% of complications in early post-operative period: four had acute pyelonephritis, two had renocutaneous fistula and one died due to respiratory failure. Mean follow-up period was 5 years, ranging from 12 months to 9.7 years. There was only one case of recurrence with the need of reoperation. Comparing pre-operative and post-operative imaging results, we found that 89% had normal renal function, 7% diminished but better than before and 2% equal as before surgery. Conclusion: Open dismembered pyeloplasty is a safe and effective treatment in paediatric UPJS.